DIFFERENTIATED INSTRUCTION FOR ENHANCING YOUNG EFL LEARNERS' BASIC VOCABULARY KNOWLEDGE: A TWO-CYCLE COMMUNITY SERVICE PROGRAM AT PPA IO-0133 KRAMMER HILINA'A - Afore Tahir Harefa; Wina Anjelina Harefa; Sharley Grace Mendrofa; Christian Pradana Putra Zalukhu; Crystian Akbar Maulana Maulana; Alvin Ebenezer Zamasi; Imel Trisna Zabua; Ria Gracia Telaumbanua; Miseri Cordias Domini Harefa; Mar Mawarti Gea (Jurnal Gembira: Pengabdian Kepada Masyarakat, 2026)
This community service project addressed the wide range of basic English vocabulary among young EFL learners at PPA IO-0133 Krammer Hilina'a Church. Using a two-cycle classroom action research design (planning, action, observation, reflection), it aimed to strengthen learners' vocabulary through differentiated instruction supported by simplified materials, songs, and games. Participants were 23 learners aged 9–11 in Class E. Quantitative data came from vocabulary tests across the cycles; qualitative data from observations, field notes, and documentation analysed with the Miles, Huberman, and Saldaña (2014) model. Learners in the Good and Very Good categories rose from 26.09% in Cycle 1 to 65.22% in Cycle 2, while Poor and Very Poor fell from 39.13% to 0%. Qualitative findings showed greater confidence, participation, and recall. Differentiated instruction combined with playful, multisensory activities is an effective, inclusive approach for developing young learners' basic vocabulary in community-based settings.